IMAGE PROCESSING FOR PERCENTAGE ANALYSIS OF VESSELS FOR VESSELS IN CORONARY HEART DISEASE PATIENTS - Agung Satrio Nugroho; Sri Arttini Dwi Prasetyowati; Arief Marwanto (Journal of Telematics and Informatics, 2020)
Cardiovascular disease is the highest cause of death worldwide, for this reason early detection is important to reduce mortality due to heart disease and blood vessels, so that a program is needed to calculate the narrowing that occurs in blood vessels experienced in patients affected by coronary heart disease, so can make it easier for a doctor to analyze and give a medical decision whether to do the ring installation or just administering drugs for blood thinning. This research uses the development of image processing technology from angiographic results by utilizing cropping to determine the area to be analyzed and image segmentation, where image segmentation is in the form of a denoise as a mean filter and increases the transmission of the image to be analyzed and thresholding which is a way of emphasizing the image by changing the image to black and white. Where the narrowing area is obtained from counting the number of logical pixels 1 of the image area that has been blocked and has been reconstructed while the normal area is calculated from the number of pixels having logic 1 plus the pixel area having logic 1, logic pixel 0 is an area of the vessel that is not narrowed. The results showed that the narrowing of the vessels in patients experienced by patients affected by coronary heart can be measured how narrowing is experienced. Of the 11 patient data measured, there were 4 patient data that were compared with the measurement results of the angiography instrument with the highest obtained error value of 3.9% and the lowest error value of 0.1% with an average value of error 1.8% where the error value is still within the tolerance value. Keywords: image processing, vessels for vessels, coronary heart disease